Business Potential of Small Fishing Communities under Sharia-Based Village Enterprises Regulation - Sandi Andika; Muhammad Ilham (LPPM ISNJ Bengkalis, 2026)
Bengkalis Regent Regulation Number 81 of 2019 was issued as the legal foundation for the development of Sharia-based Village-Owned Enterprises (BUMDes); however, its implementation has stalled due to a gap between the regulations and their operationalization. Purpose: This study aims to analyze the association between the implementation of this policy and the perceived business potential of small-scale fishermen in the coastal areas of Bengkalis Regency. Method: Employing a quantitative approach with an associative cross-sectional design, data were collected from 408 respondents via questionnaires and analyzed using simple linear regression. Findings: The results indicate that the implementation of the regulation is significantly related to the fishermen’s perceived business potential. The regression equation Y = 18.379 + 0.534X reveals an interesting finding: fishermen have a very high baseline level of potential and mental readiness, even without intervention. However, a paradox emerged: ideological support for the interest-free program is high (97.30%), whereas technical understanding of the regulatory content remains low (49.51%). The regulatory contribution of 26.4% R2 confirms that this policy is a necessary condition for legal certainty, yet operational success depends heavily on other adaptive capacity factors (73.6%). Implications: Theoretically, this study clarifies that legal certainty acts as a stimulus for economic readiness. In practice, the findings suggest that the primary barrier to Sharia BUMDes is operational literacy rather than cultural resistance. Therefore, policy dissemination must shift from normative socialization to technical guidance on Sharia contracts to effectively transform the community’s high moral capital into tangible economic participation.